Response of Carrot (Daucus carota L.) to Multi-Contaminated Soil from Historic Mining and Smelting Activities - Novák, Milan; Zemanová, Veronika; Lhotská, Marie; Pavlík, Milan; Klement, Aleš; Hnilička, František; Pavlíková, Daniela (International journal of molecular sciences, 2023)
A pot experiment was undertaken to investigate the effect of Cd, Pb and Zn multi-contamination on the physiological and metabolic response of carrot (Daucus carota L.) after 98 days of growth under greenhouse conditions. Multi-contamination had a higher negative influence on leaves (the highest Cd and Zn accumulation) compared to the roots, which showed no visible change in terms of anatomy and morphology. The results showed the following: (i) significantly higher accumulation of Cd, Zn, and Pb in the multi-contaminated variant (Multi) compared to the control; (ii) significant metabolic responses-an increase in the malondialdehyde content of the Multi variant compared to the control in the roots (by 20%), as well as in the leaves (by 53%); carotenoid content in roots decreased by 31% in the Multi variant compared with the control; and changes in free amino acids, especially those related to plant stress responses. The determination of hydroxyproline and sarcosine may reflect the higher sensitivity of carrot leaves to multi-contamination in comparison to roots. A similar trend was observed for the content of free methionine (significant increase of 31% only in leaves); (iii) physiological responses (significant decreases in biomass, changes in gas-exchange parameters and chlorophyll a); and (iv) significant changes in enzymatic activities (chitinase, alanine aminopeptidase, acid phosphatase) in the root zone.
Keywords: chlorofyl a; free amino acids; photosynthesis; zinc; Lead; Chlorophyll A; malondialdehyde; root vegetable; Soil; mrkev obecná; půda; olovo; cadmium; lead; soil enzymes; kadmium; Daucus carota; Cadmium